THE ROLE OF STAKEHOLDERSS IN POVERTY ALLEVIATION OF FISHERMAN GROUPS IN TANJUNG MAS URBAN VILLAGE, NORTH SEMARANG SUB-DISTRICT, SEMARANG CITY - Firman Saputra Napitupulu; Ari Subowo; Teuku Afrizal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Poverty is a multidimensional problem that is still difficult to get over by the Semarang City Government, especially in the North Semarang District area. This sub-district is stated as the sub-district with the second-highest poverty rate with 27,245 poor in 2020. This study aims to examines the stakeholders' network and their role in poverty alleviation programs. Grounded by the descriptive qualitative method, data collection was conducted via observation, interviews, and documentation. In this study, ten informants were selected through the purposive sampling technique. The results show that the key stakeholder is the Semarang City Social Service because it provides poverty data in Semarang. This data is the basis for providing poverty alleviation programs, including the PKH program, Smart Indonesia Card, and BPNT (Non-Cash Food Assistance). Coordinate to the North Semarang District Tanjung Mas Village as primary stakeholders who act as coordinators and facilitators in poverty alleviation. Secondary stakeholders are the Indonesian Traditional Fishermen's Union, Joint Business Group, and Head of RTs, who act as accelerators in assisting the Government in implementing poverty alleviation programs. Meanwhile, the community is a tertiary stakeholder who acts as a recipient and implementer of policies. This study concludes that there are four stakeholder networks with different roles for each stakeholder. Suggestions that can be given the need to improve coordination in the existing stakeholder network and the Social Service are also expected to provide data and be directly involved in the implementation of poverty alleviation programs.